Sistem Informasi Cuti Pegawai Berbasis Web pada Dinas Pemberdayaan Perempuan Perlindungan Anak Pemberdayaan Masyarakat dan Pengendalian Penduduk dan KB Kota Medan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
The employee leave application information system is a digital solution designed to simplify the process of submitting, approving, and managing leave within an institution. This internship project resulted in the development of a system called SiCuti, which was built using the Laravel framework with a MySQL database. The system provides two main roles: employees and administrators/supervisors. Employees can apply for leave according to their entitlements, such as annual leave with a maximum of 12 working days, maternity leave for 3 months, pilgrimage leave (Hajj) which can be taken once during their service period, as well as special leave for important reasons such as marriage or the death of an immediate family member, typically lasting 1–3 days. When applying, employees may also upload supporting documents and monitor the status of their applications through the leave status menu.Administrators or supervisors have broader authority, including reviewing the list of leave requests, approving or rejecting applications, and managing employee leave quotas to ensure compliance with regulations. In addition, administrators can track the complete leave history of employees through an integrated dashboard. This feature supports faster, more transparent, and accountable decision-making processes.The results of local testing indicate that SiCuti has the potential to increase efficiency in administrative leave processes that were previously carried out manually, making them faster, more transparent, and more structured. The interactive dashboard design also facilitates monitoring from both employees and administrators. With the implementation of SiCuti, it is expected that the leave management process can reduce the risk of human error, ensure data accuracy, and support transparency and accountability in human resource management once the system is fully deployed within the institution.